2013
DOI: 10.1371/journal.pone.0061555
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Bound Platinum Is the Major Determinant of Cisplatin Sensitivity in Head and Neck Squamous Carcinoma Cells

Abstract: PurposeThe combination of systemic cisplatin with local and regional radiotherapy as primary treatment of head and neck squamous cell carcinoma (HNSCC) leads to cure in approximately half of the patients. The addition of cisplatin has significant effects on outcome, but despite extensive research the mechanism underlying cisplatin response is still not well understood.MethodsWe examined 19 HNSCC cell lines with variable cisplatin sensitivity. We determined the TP53 mutational status of each cell line and inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…However, Holzer et al reported that an enhanced expression of hCTR1 in ovarian cancer cells induced higher accumulation of CDDP and copper but only a marginal increase in the cytotoxicity of CDDP due to improper intracellular localization of CDDP (14). Therefore, the cytotoxicity induced by CTR1 expression and CDDP in cancer cells might still be controversial (28)(29)(30), and this issue should be resolved by performing a further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, Holzer et al reported that an enhanced expression of hCTR1 in ovarian cancer cells induced higher accumulation of CDDP and copper but only a marginal increase in the cytotoxicity of CDDP due to improper intracellular localization of CDDP (14). Therefore, the cytotoxicity induced by CTR1 expression and CDDP in cancer cells might still be controversial (28)(29)(30), and this issue should be resolved by performing a further study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differences in intracellular cisplatin at AT-0 and AT-1 times revealed a considerable cisplatin efflux after one hour for all the cell lines except A2780cis, which was much higher and faster than those reported before. 14,23,37,48 In the analysis of genomic stability, the Comet assay is the most widely used tool. 34 However, detection of DNA strand breaks after cisplatin treatment is not a straightforward result; some authors reported them in different cells and organisms, 20,26 and others reported their absence.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,9,10 Since most of these processes are ultimately associated with the prevention of cisplatin-DNA adduct formation, or with their fast removal from the exposed DNA, the accurate detection and quantitation of DNA adducts may be a valuable tool in the early prediction of resistance. [11][12][13][14][15] However, there are some inconsistencies in the literature regarding the value of the cisplatin-DNA adduct level per se as a resistance predictive factor. 8,12 It has been known for several years that cisplatin treatment is able to modify cell cycle progression, [16][17][18] and that this modification could be different for sensitive and resistant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic and Fanconi anemia HNSCC cell lines were established as described previously (19)(20)(21). All three FA-HNSCC cell lines were genetically corrected.…”
Section: Cell Culturementioning
confidence: 99%